Cortical control of striatal fast‐spiking interneuron synchrony. (11th April 2022) - McKeon, Paige N.; Bunce, Garrett W.; Patton, Mary H.; Chen, Rong; Mathur, Brian N.
Abstract : Abstract: Inhibitory fast‐spiking interneurons in the dorsal striatum regulate actions and action strategies, including habits. Fast‐spiking interneurons are widely believed to synchronize their firing due to the electrical synapses formed between these neurons. However, neuronal modelling data suggest convergent cortical input may also drive synchrony in fast‐spiking interneuron networks. To better understand how fast‐spiking interneuron synchrony arises, we performed dual whole‐cell patch clamp electrophysiology experiments to inform a simple Bayesian network modelling cortico‐fast‐spiking interneuron circuitry. Dual whole‐cell patch clamp electrophysiology revealed that while responsivity to corticostriatal input activation was high in fast‐spiking interneurons, few of these neurons exhibited electrical coupling in adult mice. In simulations of a cortico‐fast‐spiking interneuron network informed by these data, the degree of glutamatergic cortical convergence onto fast‐spiking interneurons significantly increased fast‐spiking interneuron synchronization while manipulations of electrical coupling between these neurons exerted relatively little impact. These results suggest that the primary source of functional coordination of fast‐spiking interneuron activity in adulthood arises from convergent corticostriatal input activation. Key points: Electrical synapses between striatal fast‐spiking interneurons in adult mice occur in ∼8% of assayed pairs. Coincident, convergent cortical input onto fast‐spiking interneurons significantly contributes to fast‐spiking interneuron synchrony. Electrical synapses between fast‐spiking interneurons provide only minor enhancement of fast‐spiking interneuron synchrony. These results suggest a mechanism by which adult mouse fast‐spiking interneurons of the striatum synchronize in the face of declining expression of the electrical synapse‐forming connexin‐36 protein. Abstract : Abstract figure legend Dual whole‐cell patch clamp recordings of dorsal striatal fast‐spiking interneurons (FSIs; red circles) show these rarely (8%) form electrical synapses with other FSIs in adult mouse. In a two‐layer in silico model of cortical pyramidal neuron (grey triangles) input to FSIs using empirically defined cortico‐FSI synaptic weights, synchronous FSI–FSI activity (in the absence of abundant electrical synapses) is achievable by convergent cortical pyramidal excitation of FSIs.